2018
DOI: 10.1002/eji.201747287
|View full text |Cite
|
Sign up to set email alerts
|

Altered toll‐like receptor responsiveness underlies a dominant heritable defect in B cell tolerance in autoimmune New Zealand Black mice

Abstract: Systemic lupus erythematosus is a debilitating autoimmune disease in which autoantibodies and autoreactive T cells destroy kidneys and other organs. Disease is clinically and genetically heterogeneous, suggesting that underlying mechanisms vary between patients. We previously used an autoantibody transgenic mouse reporter system to examine the effect of different autoimmune backgrounds on B-cell tolerance, failure of which is a fundamental defect in lupus. We identified a defect consistent with reversible aner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 39 publications
1
5
0
Order By: Relevance
“…CXorf21 is a binding partner of another SLE-risk gene— Slc15a4 . As noted above SLC15A4 is involved in transport of oligopeptides and hydrogen ions out of the lysosome, and knockout of Slc15a4 results in abrogation of TLR7 signaling as well as amelioration of murine lupus (17, 18, 20, 21). We have shown that CXorf21 protein is expressed exclusively in monocytes, B cells, and dendritic cells, and the protein levels are two–three-fold higher in female cells compared to male cells.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…CXorf21 is a binding partner of another SLE-risk gene— Slc15a4 . As noted above SLC15A4 is involved in transport of oligopeptides and hydrogen ions out of the lysosome, and knockout of Slc15a4 results in abrogation of TLR7 signaling as well as amelioration of murine lupus (17, 18, 20, 21). We have shown that CXorf21 protein is expressed exclusively in monocytes, B cells, and dendritic cells, and the protein levels are two–three-fold higher in female cells compared to male cells.…”
Section: Discussionmentioning
confidence: 84%
“…There is increased expression of interferon-regulated genes in peripheral blood mononuclear cells from patients with either disease (710). Evidence from both human disease (1113) and murine models (1417) suggests that signaling through lysosomal, nucleic acid-binding toll-like receptors (TLR) 7 and 9 is in part responsible for the pathogenicity, including increased interferon activity in these diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Isolated lung cells from exposed B6, MRL and NZB mice were cultured with or without ligands to TLRs to assess silica-related responsivity, with and without the additional environmental (TLR) stimulus. Ligand to TLR4 or a mixture of ligands to TLR7 and TLR9 were used, based on our prior experience demonstrating additive effect of TLR7 and 9 ligands in unmasking reversible anergy in NZB lupus (20). Both TLR solutions induced anti-DNA IgM, including from lung cells of both silica- and vehicle-exposed mice; the highest levels of anti-DNA IgM were induced by TLR7/9 ligand combination (not shown).…”
Section: Resultsmentioning
confidence: 99%
“…For flow cytometry, freshly isolated red blood cell-depleted lung or spleen cell suspensions were Fcgamma Receptor blocked and stained using fluorescence (FL)-labeled Ig, and isotype controls, for CD45 (leukocytes), CD19 (B cells), CD3 (T cells), IgMa (Ig Tg), and IgMb (endogenous Ig) as previously described (19, 20). Data were acquired using FACScalibur or FACSCanto machines (BD Biosciences, San Jose, CA), and data were analyzed using FlowJo software (Ashland, OR).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation